Tujuh Budaya Tujuh Budaya Masyarakat Pegunungan: Reposisi Pesantren Sebagai Pembimbing Masyarakat - Ahmad Halid (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2021)
Culture is beliefs, norms, values, assumptions held by the community. The research method was determined by using a qualitative approach and collecting observation, interview, and documentation data. Data analysis using the Miles and Huberman model. A developed society is a society that is highly cultured and maintains its culture. Mountain culture is the culture of Amaen paraben (matchmaking), culture (aghelluk) pencak (ocular strength and kanoragan science), Magic / Guna-use culture, Toktok culture (united cattle complaints), ngalak chukok kalaot culture (mutual cooperation to catch fish) in the context of marriage or kalamam children greeting khatam al-qur'an, salvation three, seven, forty, one hundred days of death of a person or other celebration), salamatan janur katopak (village salamatan) culture and kalongan katopak and jhubethe cattle culture. These seven cultures have been selected and colored by pesantren so that it becomes a culture that is beneficial to people's lives.